ChemInform Abstract: A General and Mild Copper(I)‐Catalyzed Three‐Component Reaction of Cyanamides, Amines, and Diaryliodonium Triflates. Issue 39 (September 2016) - Li, Jihui; Wang, Hongxing; Hou, Yifeng; Yu, Weiguang; Xu, Shuying; Zhang, Yucang
Abstract: to give guanidines in good yields